Intra-annual variations and determinants of canopy layer urban heat island in China using remotely sensed air temperature and apparent temperature - Li, Yuanzheng; Feng, Zhizhi; Ma, Chaoqun; Yang, Tengbo; Qiao, Fucheng; Kang, Peng; Sun, Yongsheng; Wang, Lan (Ecological indicators, 2024)
[Display omitted] •Intra-annual changes of CLUHIs were explored in China using remotely sensed air temperature and apparent temperature.•Comparisons were conducted among various CLUHIs and SUHIs.•Twelve determinants were studied for CLUHIIs based on diverse temperature indices under various ecological contexts. Canopy layer urban heat island (CLUHI) is closely related to about 4.7 billion urban residents’ well-being. Compared with sparse observation stations, remote sensing can obtain spatially continuous temperature, which is conducive to intra-annual variation and associated factors of CLUHI over large regions. Such research is scarce, especially from apparent temperature perspective. Thus, the intra-annual spatio-temporal variations and twelve determinants of CLUHI intensities (CLUHIIs) were investigated for 917 urban region agglomerations in China’s five ecological regions, using remotely sensed near-surface air temperature, apparent temperature and other multi-source data, and several spatial analysis and mathematical statistic methods. The findings revealed that annual CLUHIIs by mean temperatures were most between 0.5 and 1.0 ℃, higher in the summer and spring, and larger in North China than South China in the summer. The annual CLUHIIs by maximum temperatures were negative in several cities, especially in rainless West China. North China generally had stronger CLUHIIs by minimum temperatures in all seasons compared to South China. The CLUHIIs by mean apparent temperatures were larger in the summer (most between 0.5 and 2.0 ℃) and varied across ecological regions. Significant positive correlations generally existed among CLUHIIs by various air temperature and land surface temperature indices (p < 0.05). Nevertheless, obvious differences existed among them. The CLUHII was significantly negatively partially correlated with total precipitation, urban–rural difference in enhanced vegetation index and albedo, positive with urban–rural difference in nighttime light intensity, population density, sulfur dioxide concentration, insignificant with total population, urban area size and landscape shape index in different degree. These findings provided valuable insights into CLUHI research.